2011
DOI: 10.1007/978-3-642-23342-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Fungi and Their Role in Corals and Coral Reef Ecosystems

Abstract: Fungi in coral reefs exist as endoliths, endobionts, saprotrophs and as pathogens. Although algal and fungal endoliths in corals were described way back in 1973, their role in microboring, carbonate alteration, discoloration, density banding, symbiotic or parasitic association was postulated almost 25 years later. Fungi, as pathogens in corals, have become a much discussed topic in the last 10 years. It is either due to the availability of better tools for investigations or greater awareness among the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 85 publications
1
24
0
1
Order By: Relevance
“…Endolithic fungi have been shown to elicit a defensive response in corals, and have thus been suggested to elicit a parasitic, rather than saprophytic (or mutualistic) nature of association (Le Campion-Alsumard et al, 1995; Bentis et al, 2000; Golubic et al, 2005; Raghukumar and Ravindran, 2012). Perhaps the most striking example for potential parasitism has been the study of Aspergillus sydowii , a common terrestrial fungus suggested to cause an epidemic in the sea fan Gorgonia ventalina that can also confer symptoms to G. flabellum (Geiser et al, 1998; Kim and Harvell, 2004).…”
Section: Coralsmentioning
confidence: 99%
“…Endolithic fungi have been shown to elicit a defensive response in corals, and have thus been suggested to elicit a parasitic, rather than saprophytic (or mutualistic) nature of association (Le Campion-Alsumard et al, 1995; Bentis et al, 2000; Golubic et al, 2005; Raghukumar and Ravindran, 2012). Perhaps the most striking example for potential parasitism has been the study of Aspergillus sydowii , a common terrestrial fungus suggested to cause an epidemic in the sea fan Gorgonia ventalina that can also confer symptoms to G. flabellum (Geiser et al, 1998; Kim and Harvell, 2004).…”
Section: Coralsmentioning
confidence: 99%
“…The heterotrophic microbial endoliths include a few documented parasitic species in the Ascomycota (true fungi) and Labyrinthulomycota (Stramenopilia) (Kohlmeyer 1969; Raghukumar and Lande 1988; Porter and Lingle 1992; Golubec et al 2005; Raghukumar and Ravindran 2012) and these aggressive species may attack and feed on the photosynthetic endoliths. The heterotrophic endoliths are thought to release proteolytic enzymes which facilitate the breakdown of proteins left over from the process of formation of the shells by the animals.…”
Section: Characteristics Of Rock Transforming Fungimentioning
confidence: 99%
“…Although fungi undoubtedly play many important ecological roles in coral ecosystems, they have been largely ignored in the past (Bentis et al 2000). Our current and very limited knowledge of the roles of fungi in corals and coral reef ecosystems has been reviewed in detail by Raghukumar and Ravindran (2012). Corals, lichens and mycorrhizae are all symbiotic relationships involving fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Many species of fungi are known to bore into solid rock, sand grains and shells and can cause disease in many animal and plant tissues in marine ecosystems (Rosenberg and Ben-Haim 2002; Golubic et al 2005; Pitt and Hocking 2009; Raghukumar and Ravindran 2012; Burge et al 2013). In this review, we discuss what is known about the different ecotypes of Ascomycota (true fungi) with emphasis on anamorphic stages of Aspergillus sydowii and other species, which bore into skeletons of corals or shells of molluscs and infect the soft tissues of these animals causing diseases in marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%